Synergistic Microbicidal Effect of Auranofin and Antibiotics Against Planktonic and Biofilm-Encased S. aureus and E. faecalis - She, Pengfei; Zhou, Linying; Li, Shijia; Liu, Yiqing; Xu, Lanlan; Chen, Lihua; Luo, Zhen; Wu, Yong (Frontiers in Microbiology, 2019)
Methicillin-resistant/susceptible Staphylococcus aureus (MRSA/MSSA) and Enterococcus faecalis strains are often found in community- and hospital-acquired infections. The single use of conventional antibiotics hardly completely kills the bacterial cells of interest, especially in the form of biofilms. Thus, drug repurposing and antimicrobial combination are promising ways to solve this problem. Antimicrobial susceptibility assays against cocci in a suspension and in a biofilm mode of growth were performed with broth microdilution methods. Checkerboard assays and the cutaneous mouse infection model were used to examine the activity of auranofin and conventional antibiotics alone and in combination. In the present study, auranofin possesses potent antimicrobial activities against both planktonic cells and biofilms with minimum inhibitory concentrations ranging 0.125-0.5 mg/L. Auranofin in combination with linezolid or fosfomycin showed synergistic antimicrobial activities against S. aureus MSSA and MRSA both in vitro and in vivo. Similarly, auranofin also behaved synergistic effect with chloramphenicol against E. faecalis. Additionally, auranofin improved the antibiofilm efficacy of chloramphenicol and linezolid, even on the biofilms grown on a catheter surface. Though, S. epidermidis showed significant susceptibility to AF treatment, no synergistic antimicrobial effects were observed with antibiotics we tested. In all, the use of a combination of auranofin with linezolid, fosfomycin and chloramphenicol can provide a synergistic microbicidal effect in vitro and in vivo, which rapidly enhances antimicrobial activity and may help prevent or delay the emergence of resistance.